Safety Culture Intervention Strategies to Enhance Patient Incident Reporting: Systematic Literature Review : JEL Classification: I10, I18, M12, M14, O33 - Amry Irsyada Yusuf; Safari Wahyu Jatmiko; Imronudin Imronudin (Newinera Publisher, 2025)
Improving patient safety incident reporting is essential to strengthen safety culture and prevent adverse events in hospitals. We aimed to identify safety culture intervention strategies to improve patient safety incident reporting. This study was conducted using a systematic data search following the PRISMA method through PubMed, Scopus, and Google Scholar databases to identify interventional studies published between 2015 and 2025. The main keywords included “patient safety, interventions, training, program, incident reporting, adverse event reporting, error reporting.” The findings were identified and organized through thematic categorization based on the Self-Protective Behavior Framework. The most prevalent and promising approach is multifaceted intervention. Key strategies, including education and training, feedback mechanisms, management support, and technology integration, showed consistent positive results with improved reporting rates. Improving incident reporting effectively requires a multifaceted strategy. Education and training must be reinforced by continuous feedback, strong leadership, and streamlined technology to build a sustainable and non-punitive reporting culture.